Normobaric hypoxia reduces V.O2 at different intensities in highly trained runners - Sharma, A. P.; Saunders, P. U.; Garvican-Lewis, L.; Clark, B.; Gore, C. J.; Thompson, K. G.; Périar, J. D. (Medicine & Science in Sports & Exercise, 2019)
Introduction We sought to determine the effect of low and moderate normobaric hypoxia on oxygen consumption and anaerobic contribution during interval running at different exercise intensities. Methods Eight runners (age, 25 ± 7 yr, V O2max: 72.1 ± 5.6 mL/kg·min) completed three separate interval sessions at threshold (4 × 5 min, 2-min recovery), V O2max (8 × 90 s, 90-s recovery), and race pace (10 × 45 s, 1 min 45 s recovery) in each of; normoxia (elevation: 580 m, FiO2: 0.21), low (1400 m, 0.195) or moderate (2100 m, 0.18) normobaric hypoxia. The absolute running speed for each intensity was kept the same at each altitude to evaluate the effect of FiO2 on physiological responses. Expired gas was collected throughout each session, with total V O2 and accumulated oxygen deficit calculated. Data were compared using repeated-measures ANOVA. Results There were significant differences between training sessions for peak and total V O2, and anaerobic contribution (P < 0.001, P = 0.01 respectively), with race pace sessions eliciting the lowest and highest responses respectively. Compared to 580 m, total V O2 at 2100 m was significantly lower (P < 0.05), and anaerobic contribution significantly higher (P < 0.05) during both threshold and V O2max sessions. No significant differences were observed between altitudes for race pace sessions. Conclusions To maintain oxygen flux, completing acute exercise at threshold and V O2max intensity at 1400 m simulated altitude appears more beneficial compared with 2100 m. However, remaining at moderate altitude is a suitable when increasing the anaerobic contribution to exercise is a targeted response to training.